1997
DOI: 10.1093/glycob/7.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Mouse β-galactoside α2,3-sialyltransferases: comparison of in vitro substrate specificities and tissue specific expression

Abstract: Four types of beta-galactoside alpha 2,3-sialyltransferase (ST3Gal I-IV) have been cloned from several animals, but some contradictory observations regarding their substrate specificities and expression have been reported. Therefore, it is necessary to concurrently analyze the substrate specificities of the four enzymes, of which the source should be one animal. Accordingly, the acceptor substrate specificities and gene expression of mST3Gal I-IV were analyzed. Since we had already cloned ST3Gal I and II, as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 19 publications
3
121
1
Order By: Relevance
“…These values are in good agreement with the data previously obtained with the same enzyme expressed in COS cells (21,22). Rather similar apparent K m values toward the donor substrate have been obtained for the four mutants tested thus confirming the behavior of these mutants in CDP binding tests (Fig.…”
Section: Expression Of Hst3gal I and Mutants In Insectsupporting
confidence: 91%
See 1 more Smart Citation
“…These values are in good agreement with the data previously obtained with the same enzyme expressed in COS cells (21,22). Rather similar apparent K m values toward the donor substrate have been obtained for the four mutants tested thus confirming the behavior of these mutants in CDP binding tests (Fig.…”
Section: Expression Of Hst3gal I and Mutants In Insectsupporting
confidence: 91%
“…ST3Gal I transfers Neu5Ac to the galactose residue of type 3 disaccharide found on glycolipids or O-glycosyl proteins. Kinetic studies have shown that ST3Gal I exhibits high transfer efficiency and high affinity (K m of 51 M) toward the core 1 mucin type disaccharide Gal␤1-3GalNAc␣- (21). Therefore, this enzyme was considered as a good candidate for structure-function studies and for further crystallization trials.…”
mentioning
confidence: 99%
“…However, it is equally likely that this high number of enzymes have evolved as a result of specific requirements for enzymes with different functions. Apparent redundancies in substrate specificities of glycosyltransferases have been found in sialyltransferases (28,29), fucosyltransferases (30 -32), ␤4-galactosyltransferases (2-4), and polypeptide GalNAc-transferases (14,33). There are differences in the kinetic parameters of some members of each of these families that relate to type and complexity of acceptor glycoconjugate or acceptor peptide sequence for the polypeptide GalNAc-transferases.…”
Section: Discussionmentioning
confidence: 99%
“…ST3Gal-3 2 HL-60s displayed ;35% reduction in CLA expression, consistent with the notion that this enzyme shows higher activity toward type I (Galb1,3GlcNAc) rather than type II (Galb1,4Glc-NAc) LacNAc. 20 Silencing ST3Gal-6 augmented CLA expression by .twofold, though the precise reason for this is unknown. Similar observations, as with HECA-452, were made when mAb CSLEX-1 measured cell-surface sLe X expression ( Figure 2E).…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Regulation Of mentioning
confidence: 99%
“…16,17 We sought to identify the human a2,3 sialyltransferases (sialylTs) that regulate myeloid cell rolling on selectins. In this regard, among the 6 mammalian a2,3sialyTs (ST3Gal-1-6), we choose to focus on ST3Gal-3, -4, and -6 because these enzymes transfer sialic acid (NeuAc in humans) to the 3-position of galactose on type II n-Acetyllactosamine/LacNAc (Galb1,4GlcNAc) structures to generate sLe X and related glycans [18][19][20][21][22] ( Figure 1). Among these, ST3Gal-3 also acts on type I lactosamine substrates (Galb1,3GlcNAc) to create sialyl Lewis-a (sLe a )-type epitopes.…”
Section: Introductionmentioning
confidence: 99%